Method for extracting lithium and copper from organic acid immersion liquid of waste lithium iron phosphate battery
By using pH-responsive copper adsorbent in the organic acid soaking liquid of waste lithium iron phosphate batteries for Cu2+ adsorption and desorption, combined with chemical precipitation method, the problem of poor copper selectivity is solved, and efficient recovery of lithium and copper and full utilization of resources is achieved.
Patent Information
- Application Number
- CN202411776019.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art When extracting lithium and copper from organic acid leachate liquid of waste lithium iron phosphate batteries, the selectivity of copper is poor, resulting in difficulty in lithium recycling and copper loss.
The pH-responsive copper adsorbent was used to adsorb and desorb Cu2+ in the organic acid soaking solution of waste lithium iron phosphate batteries, and then Li3PO4 and Cu2P2O7 products were obtained by chemical precipitation.
It realizes efficient selective separation of lithium and copper, reduces the need for subsequent decomposition purification steps, makes full use of the metal resources in the acid soaking liquid, and improves the efficiency of battery resource recycling.
Smart Images

Figure CN119614869A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for extracting metals from organic acid leaching solution of waste lithium iron phosphate batteries, and in particular to a method for extracting lithium and copper from organic acid leaching solution of waste lithium iron phosphate batteries, belonging to the field of waste battery element recovery. Background Art
[0002] As energy and environmental issues become increasingly prominent, the electric vehicle industry has achieved rapid development, greatly stimulating the research and development and manufacturing of the battery field. Lithium iron phosphate (LFP) batteries are widely used in electric vehicles due to their wide range of raw material sources, high structural stability and long service life. However, as the years of use increase, these batteries will eventually face the fate of being scrapped. A large number of discarded LFP batteries are both a "urban mine" resource and a source of environmental pollution. Therefore, recycling these resources is not only in line with the energy development strategy, but also conducive to promoting the realization of the "dual carbon" goal.
[0003] At present, the main methods for recycling waste lithium iron phosphate (SLFP) batteries are pyrometallurgy, hydrometallurgy and direct regeneration. Hydrometallurgy is widely used in battery recycling due to its high recovery rate. Among them, organic acid leaching is considered to be an efficient, green and sustainable method for recycling SLFP batteries. Although the leaching rate of organic acid for iron (Fe) is extremely low, its selectivity for copper (Cu) is poor, resulting in a large amount of Cu in the leaching solution. 2+ This will not only cause difficulties in lithium recovery, but also cause copper losses. Summary of the invention
[0004] In view of this, the present invention provides a method for extracting lithium (Li) and copper (Cu) from organic acid leaching solution of discarded lithium iron phosphate (SLFP) batteries, which not only fully recovers the lithium resources in the SLFP batteries, but also further makes full use of the copper resources to obtain Li3PO4 and Cu2P2O7 products.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for extracting lithium and copper from organic acid leaching solution of waste lithium iron phosphate batteries, the steps are as follows:
[0007] S1. Add pH-responsive copper adsorbent to the organic acid leaching solution of waste lithium iron phosphate battery and mix thoroughly. 2+ Adsorption;
[0008] S2. After the adsorption, centrifuge and dry the precipitate, then add it to the desorption solution for Cu 2+ Desorption;
[0009] S3, after the desorption is completed, the desorption liquid is evaporated and concentrated, and a conversion agent is added to obtain copper hydroxide solid;
[0010] S4, mixing copper hydroxide solid and diammonium hydrogen phosphate solid and reacting them at high temperature to obtain copper pyrophosphate (Cu2P2O7);
[0011] S5, concentrating the upper layer liquid after centrifugation in S2 and adjusting the pH value for purification to obtain a purified liquid;
[0012] S6. Add a precipitant to the purified liquid to precipitate lithium phosphate, centrifuge and dry to obtain lithium phosphate solid.
[0013] On the basis of the above technical solution, the present invention further defines the solution as follows:
[0014] Furthermore, the organic acid in S1 is succinic acid; the parameters of the shaking table are set as: 45°C, 170r / min.
[0015] Furthermore, the centrifugal speed in S2 is 6000-8000 r / min, and the desorption parameters are: 45°C, 170 r / min.
[0016] Furthermore, the concentration conditions in S3 are: 95°C, 300r / min, and the concentration multiple is 15 to 20 times;
[0017] The conversion agent is 2 mol / L sodium hydroxide solution.
[0018] Further, the molar ratio of copper hydroxide solid to diammonium hydrogen phosphate solid in S4 is 3:2;
[0019] The temperature of the high temperature reaction is 850°C and the time is 10 hours.
[0020] Furthermore, the concentration conditions in S5 are 95°C, 30r / min, and the concentration multiple is 4 to 5 times;
[0021] The pH value was adjusted using 2 mol / L sodium hydroxide solution.
[0022] Further, the centrifugal speed in S6 is 5000-6000 r / min, and the drying temperature is 60°C;
[0023] The precipitant is solid sodium phosphate dodecahydrate, which reacts with the Li + The molar ratio is 1.2:1.
[0024] Furthermore, the pH-responsive copper adsorbent was H-CAOMIL, and the ratio of H-CAOMIL to organic acid leaching solution was 40 mL / g;
[0025] The desorption solution was 0.05 mol / L nitric acid solution, and the ratio of H-CAOMIL to desorption solution was 100 mL / g;
[0026] Among them, H-CAOMIL is obtained by mixing an aqueous solution of aluminum nitrate nonahydrate with 1,2,4,5-benzenetetracarboxylic acid and heating them for reaction, activating the reaction product by vacuum drying, mixing it with a lithium hydroxide solution for sufficient reaction, centrifuging and drying it, and acidifying it with dilute hydrochloric acid;
[0027] Furthermore, the pH-responsive copper adsorbent can also be made of yolk-shell type pH-responsive Fe3O4@PMAA magnetic composite microspheres, which can be prepared by distillation precipitation and RAFT active polymerization. The magnetic and pH-responsive properties of the composite microspheres can be used as metal ion adsorbents, and the maximum adsorption capacity of copper ions can reach 3.72 mmol / g.
[0028] The beneficial effects of the present invention are:
[0029] The selective separation of Li and Cu in the leaching solution by adsorption reduces the subsequent impurity removal and purification steps, further utilizes other metal resources in the acid leaching solution, and is more conducive to the resource recycling of SLFP batteries.
[0030] The introduction of the adsorption method effectively couples the chemical precipitation method for the recovery and reuse of elements, further reducing the use of precipitants and energy consumption, and is more conducive to the preparation of pure chemicals. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the process of recovering Li and Cu by coupling the adsorption method with the chemical precipitation method;
[0032] Figure 2 is a schematic diagram of the X-ray powder diffraction pattern of copper pyrophosphate;
[0033] Figure 3 This is the Fourier infrared spectrum of copper pyrophosphate;
[0034] Figure 4 This is a scanning electron microscope image of copper pyrophosphate;
[0035] Figure 5 is a schematic diagram of the X-ray powder diffraction pattern of lithium phosphate;
[0036] Figure 6 This is the Fourier infrared spectrum of lithium phosphate;
[0037] Figure 7 This is a scanning electron microscope image of lithium phosphate; DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] H-CAOMIL as Cu 2+ The adsorbent was investigated at adsorption temperature, and the adsorption temperature was set at 25℃, 35℃, 45℃, and 55℃, the adsorption liquid-solid ratio was 80mL / g, the adsorption time was 24h, the adsorption liquid was 0.1M succinic acid acid leaching solution, and the copper ion concentration in the acid leaching solution was 507mg / L; the desorption temperature was 45℃, the desorption liquid-solid ratio was 100mL / g, the desorption time was 9h, and the desorption number was once. The results are shown in Table 1.
[0041] Table 1 Adsorption capacity and desorption rate
[0042]
[0043] Example 2
[0044] The adsorbent in Example 1 was used to investigate the adsorption liquid-solid ratio, the adsorption temperature was set to 45°C, the liquid-solid ratio was set to 40, 50, 60, 80, 100, 120 mL / g, the adsorption time was 24 h, and the adsorption liquid was the acid leaching solution in Example 1; the desorption temperature was 45°C, the desorption liquid-solid ratio was 100 mL / g, the desorption time was 9 h, and the desorption number was once. The results are shown in Table 2.
[0045] Table 2 Adsorption capacity and desorption rate
[0046]
[0047]
[0048] Example 3
[0049] The adsorption time was investigated using the adsorbent in Example 1, with the adsorption temperature set to 45°C, the liquid-to-solid ratio set to 40 mL / g, and the adsorption time set to 1, 3, 7, 12, and 24 h. The results are shown in Table 3.
[0050] Table 3 Changes of adsorption capacity over time
[0051]
[0052] Example 4
[0053] The adsorbent in Example 1 was used for succinic acid leaching solution 1 (pH=5.35) and succinic acid leaching solution 2 (pH=4.21), with the adsorption temperature set to 45°C, the liquid-solid ratio set to 60 mL / g, and the time set to 24 h. The results are shown in Table 4.
[0054] Table 4 Adsorption capacity
[0055]
[0056]
[0057] Example 5
[0058] The adsorption separation ratio was investigated using the adsorbent in Example 1. The adsorption temperature was set to 45°C, the liquid-solid ratio was set to 40 mL / g, and the adsorption time was set to 24 h. The results are shown in Table 5.
[0059] Table 5 Adsorption separation ratio results
[0060] <![CDATA[Cu 2+ ]]> <![CDATA[Fe 3+ ]]> <![CDATA[Li + ]]> <![CDATA[Concentration C0 (mg / L) before adsorption]]> 395 42 1280 <![CDATA[Concentration C after adsorption e (mg / L)]]> 2 33 1215 Adsorption capacity Qe (mg / g) 15.72 0.36 2.6 <![CDATA[Partition coefficient Kd M (mL / g)]]> 7860 10.9 2.14
[0061] It can be seen from Tables 3, 4 and 5 that H-CAOMIL not only has high Cu 2+ The adsorption capacity and excellent separation performance also have good applicability to different acid leaching solutions, indicating that the introduction of this adsorbent has high practical value for the separation and recovery of Li and Cu in the acid leaching solution.
[0062] Example 6
[0063] The adsorbent after adsorption in Example 3 was used for desorption, and the desorption time was investigated. The desorption temperature was set to 45°C, the desorption liquid-solid ratio was set to 100 mL / g, 0.05 M nitric acid solution was used as the desorption liquid, and the desorption time was set to 1, 2, 3, 5, 7, and 9 h. The results are shown in Table 6.
[0064] Table 6 Desorption capacity and desorption rate
[0065]
[0066]
[0067] Example 7
[0068] The desorption solution described in Example 6 was concentrated, the heating device was a laboratory oil bath, the temperature was set to 95°C, the speed was set to 300r / min, the concentration multiple was set to 15-20 times, and the time was 4-6h. The concentrated solution was blue, and the copper ions were precipitated with a 2mol / L sodium hydroxide solution. The results are shown in Table 7.
[0069] Table 7 Ion concentration and precipitation rate of concentrated solution and electrolyzed solution
[0070] <![CDATA[Cu 2+ ]]> <![CDATA[Fe 3+ ]]> <![CDATA[Li + ]]> <![CDATA[Concentrate concentration C n (mg / L)]]> 1610 23 152.1 <![CDATA[Concentration C of the solution after precipitation p (mg / L)]]> 0.2 0.04 142.4 Sedimentation rate (%) 99.9 99.8 6
[0071] Example 8
[0072] The Cu(OH)2 precipitate in Example 7 was reacted with diammonium hydrogen phosphate ((NH4)2HPO4) at high temperature. Before the reaction, the Cu(OH)2 and (NH4)2HPO4 were fully ground and mixed in a mortar, and the molar ratio of Cu(OH)2 to (NH4)2HPO4 was controlled at 3:2. The reaction temperature was set to 850°C and the reaction time was set to 10h. The results are shown in Table 8. Figure 2 , Figure 3 , Figure 4 shown.
[0073] Table 8 Amount of substances before and after the reaction, as well as the yield and yield
[0074] <![CDATA[Cu(OH)2]]> <![CDATA[(NH4)2HPO4]]> <![CDATA[Cu2P2O7]]> Before reaction (g) 0.5985 0.555 0 After reaction (g) 0 0 0.6828 Yield (%) 0 0 97
[0075] Example 9
[0076] The post-adsorption acid leaching solution in Example 5 was concentrated at a concentration temperature of 95° C., a concentration multiple of 4 to 5 times, and a concentration time of about 3 to 4 hours. After concentration, it was purified using a 2 mol / L sodium hydroxide solution, and the pH of the solution was adjusted to about 12. The results are shown in Table 9.
[0077] Table 9 Concentrated solution ion concentration
[0078] <![CDATA[Cu 2+ ]]> <![CDATA[Fe 3+ ]]> <![CDATA[Li + ]]> <![CDATA[Concentrate concentration C n (mg / L)]]> 0 0 4810 <![CDATA[Purified concentration C p (mg / L)]]> 0 0 4740
[0079] Example 10
[0080] The evolved solution in Example 9 was subjected to a lithium precipitation experiment, using sodium phosphate dodecahydrate (Na3PO4·12H2O) as a lithium precipitation agent, the lithium precipitation temperature was set to room temperature, the molar ratio of Na3PO4·12H2O to lithium ions in the solution was set to about 0.6 to 1:1, and the solid Na3PO4·12H2O solid was mixed with the solution before solids were smoothly precipitated under the action of ultrasound, the ultrasound frequency was set to 100, the ultrasound time was set to 5 minutes, and the generated solid was centrifuged, the centrifuge speed was set to 7000 to 8500 r / min, and the time was set to 4 minutes. The results are shown in Table 10. Figure 5 , Figure 6 , Figure 7 shown.
[0081] Table 10 Ion concentration and lithium precipitation rate after lithium precipitation
[0082] <![CDATA[Li + ]]> <![CDATA[Concentration C after lithium precipitation p (mg / L)]]> 560 Lithium phosphate mass (g) 0.75 Lithium deposition rate (%) 88.2
[0083] By comparing Table 7, Table 8, Table 9 and Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 From the analysis, it can be seen that the adsorption method coupled with chemical precipitation can not only achieve the comprehensive utilization of elements in the acid leaching solution and realize a higher atomic utilization rate, but also achieve a high degree of separation and purification goals, providing a pioneering idea for the recovery of elements in the acid leaching solution of waste batteries.
Claims
1. A method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries, characterized in that: Here are the steps: S1. Add pH-responsive copper adsorbent to the organic acid leaching solution of waste lithium iron phosphate battery and mix thoroughly. 2+ Adsorption; S2. After the adsorption, centrifuge and dry the precipitate, then add it to the desorption solution for Cu 2+ Desorption; S3, after the desorption is completed, the desorption liquid is evaporated and concentrated, and a conversion agent is added to obtain copper hydroxide solid; S4, mixing copper hydroxide solid and diammonium hydrogen phosphate solid and reacting them at high temperature to obtain copper pyrophosphate; S5, concentrating the upper layer liquid after centrifugation in S2 and adjusting the pH value for purification to obtain a purified liquid; S6. Add a precipitant to the purified liquid to precipitate lithium phosphate, centrifuge and dry to obtain lithium phosphate solid.
2. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The organic acid in S1 is succinic acid; the parameters of the shaking table are set to: 45°C, 170r / min.
3. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The centrifugal speed in S2 is 6000-8000 r / min, and the desorption parameters are: 45°C, 170 r / min.
4. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The concentration conditions in S3 are: 95°C, 300r / min, and the concentration multiple is 15 to 20 times.
5. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The molar ratio of copper hydroxide solid to diammonium phosphate solid in S4 is 3:2; The temperature of the high temperature reaction is 850°C and the time is 10 hours.
6. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The concentration conditions in S5 are 95°C and 30 r / min, and the concentration multiple is 4 to 5 times.
7. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The centrifugal speed in S6 is 5000-6000 r / min, and the drying temperature is 60°C.
8. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 1, characterized in that: The conversion agent in S3 is 2 mol / L sodium hydroxide solution; In S5, the pH value was adjusted with 2 mol / L sodium hydroxide solution; The precipitant in S6 is solid sodium phosphate dodecahydrate, which reacts with the Li + The molar ratio is 1.2:
1.
9. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to any one of claims 1 to 8, characterized in that: The pH-responsive copper adsorbent is H-CAOMIL, and the ratio of H-CAOMIL to organic acid leaching solution is 40 mL / g; The desorption solution was a 0.05 mol / L nitric acid solution, and the ratio of H-CAOMIL to the desorption solution was 100 mL / g.
10. The method for extracting lithium and copper from organic acid leaching solution of discarded lithium iron phosphate batteries according to claim 9, characterized in that: H-CAOMIL is prepared by mixing an aqueous solution of aluminum nitrate nonahydrate with 1,2,4,5-benzenetetracarboxylic acid and heating the mixture. The reaction product is activated by vacuum drying, mixed with a lithium hydroxide solution for full reaction, centrifuged and dried, and acidified with dilute hydrochloric acid to obtain the product.